Women, and Land and Property Rights in Benin City, Nigeria - Yesufu, Sumaina; Nkomo, Thobeka S. (Southern African Journal of Social Work and Social Development, 2018)
The Centre on Housing Rights and Evictions states that women’s rights to land and property are systematically denied, and that over one billion women worldwide have been affected by this trend. In Nigeria, although the constitution prohibits all forms of discrimination against women, land and property rights are still determined by the principle of male primogeniture. This paper discusses the consequences of gender discrimination on women and their households in relation to land and property rights. A qualitative approach was adopted in this study. Twenty women who constituted the sample participated in the semi-structured interviews. For the focus groups discussion, the researcher selected 10 of these participants, who were divided into two focus groups. The research tools were a semi-structured interview schedule and a focus group discussion guide. The researcher analysed the data generated using thematic content analysis. The prominent findings of this paper are that housing and food insecurity, the lack of access to matrimonial property, disinheritance, and poverty are among the consequences of gender discrimination on women and their households in relation to land and property rights.